Analisis Risiko Pajanan Pm10, Pm2,5 dan Hidrokarbon di Lingkungan Kerja - Erna Veronika; Meithyra Melviana Simatupang; Ahmad Irfandi; Veza Azteria; Mayumi Nitami (Universitas Malahayati Lampung, 2025)
ABSTRACT Industrial emissions release various types of pollutants into both the atmosphere and the occupational environment. Air pollutants in the workplace may originate from production machinery or the fuels used. Chronic exposure to air contaminants in occupational settings can pose significant health risks to workers. Through environmental Health Risk Assessment (EHRA), it is possible to identify potential hazards and quantitatively estimate the associated health risks to workers. This study aims to analyze the level of exposure risk to PM2.5, PM10, and hydrocarbons in the workplace, and to evaluate the prevalence of respiratory symptoms among exposed workers. This research employed a descriptive quantitative approach with a cross-sectional study design. The analysis was conducted using the risk assessment methodology. The study population consisted of production workers, selected using a simple random sampling technique. The risk characterization revealed that the concentrations of PM10 and PM2,5 were within acceptable safety thresholds (Risk Quotient [RQ] 1), indicating a low risk of non-carcinogenic effects. However, hydrocarbon exposure exceeded the safe threshold (RQ 1), classifying it as a health risk for exposed workers. Hydrocarbon exposure in the workplace is categorized as unsafe and poses a non-carcinogenic risk to workers with an average body weight of 66.48 kg, an exposure duration of 7.583 hours per day, and an exposure frequency of 236.99 days per year over a span of 12.85 years. It is recommended that workers consistently comply with the use of personal protective equipment (PPE), particularly face masks, to mitigate the adverse health effects associated with hydrocarbon exposure. Keywords: Environmental Health Risk Assessment, PM₁₀ and PM₂,5, hydrocarbons ABSTRAK Emisi yang dihasilkan oleh industri melepaskan berbagai jenis polutan ke atmosfer maupun ke lingkungan kerja. Polutan udara di lingkungan kerja dapat berasal dari mesin produksi maupun bahan bakar yang digunakan. Adanya paparan udara pencemar dalam jangka panjang di lingkungan kerja dapat menimbulkan bahaya terhadap pekerja. Dengan studi ARKL, kita dapat mengidentifikasi risiko dan menghitung secara kuantitatif tingkat risiko kesehatan yang dapat timbul terhadap kesehatan pekerja. Penelitian ini bertujuan untuk menganalisis besar risiko pajanan PM2,5, PM10 dan hidrokarbon di lingkungan kerja serta gangguan pernafasan yang dialami oleh pekerja. Studi ini merupakan penelitian kuantitatif deskriptif dengan desain cross sectional dengan teknik analisis menggunakan metode risk assessment. Poluasi penelitian adalah pekerja di bagian produksi dengan menggunakan simple random sampling. Hasil perhitungan besar risiko menunjukkan konsentrasi polutan PM10, dan PM2,5 menunjukkan tingkat risiko masih dalam batas aman (RQ1), sedangkan pajanan Hidrokarbon masuk dalam kategori tidak aman (RQ1). Pajanan Hidrokarbon masuk dalam kategori tidak aman dan memiliki risiko nan karsinogenik bagi pekerja yang memiliki berat badan 66,48 kg dengan durasi pajanan 7,583 jam per hari dan frekuensi pajanan 236,99 hari dalam setahun selama 12,85 tahun. Di sarankan kepada pekerja untuk selalu patuh dalam menggunakan APD yaitu masker selama berada di lingkungan kerja. Kata Kunci: Analisis Risiko Kesehatan Lingkungan, PM2,5, PM10, Hidrokarbon